Karakteristik Geokimia Fluida Reservoar Pada Mata Air Panas Jengglong dan Pablengan, Kabupaten Karanganyar, Jawa Tengah - Hurien Helmi (Retii, 2022)
The old and young Lawu Mt complex exhibit significant geothermal manifestation indicate a promising geothermal potentials. The occurence of geothermal manifestations around the volcano whether it is in the upflow and outflow zones may indicates the occurrence of geothermal system in the area and is an interesting subject to be investigated. We analyze the geochemistry characteristic of reservoar fluids at Pablengan and Jengglong hotsprings to estimate the temperature at depth. We analyze the existing geological, lineament maps as well as conducting geochemistry analysis using Cl-:SO4-:HCO3-, Cl-:B:Li, and Na:K:Mg triangle diagrams. Our analysis indicate that the type of the geothermal fluids for both springs is dominated by chloride water and came from an old geothermal system. We estimate a reservoar temperature of 63oC- 155oC for Pablengan and 84oC - 182oC for Jengglong spring. The Pablengan manifestation appears to be controlled by fault as it is located only 200 meters from mapped fault while the closest fault from Jengglong manifestation is located ~2km from the spring and does not directly controlled the manifestation. Our study indicate a promising temperature range at depth, more detailed analysis of the subsurface condition is necessary to reveal its full potentials.